Collection development and preservation of indigenous knowledge in selected federal university Libraries in South West, Nigeria (2017)
In view of the importance of indigenous knowledge in development process, this paper investigated the efforts of selected federal university libraries in South West, Nigeria in indigenous knowledge collection development and preservation. The study adopted a descriptive survey design that involved the use structured questionnaire, unstructured interviews and observation as instruments for data collection. Seventy six (76) professional librarians constituted the target population of the study; therefore seventy six (76) copies of questionnaire were administered to the professional librarians in the selected university libraries. The data collected using the questionnaire complemented by interview and observation were analyzed using Statistical Package for Social Sciences (SPSS). Findings from the study revealed the tremendous efforts of selected university libraries in IK collection development and preservation in the libraries as the study revealed the existence of IK materials. It also established that dearth of fund and linguistic problem were the challenges facing the collection development and preservation of IK in the selected university libraries. It therefore recommended that the university libraries should liaised with the international bodies for financial support for the sustainability of IK resources collection development and preservation in the libraries.